Immune checkpoint inhibitor-related myositis and myocarditis: diagnostic pitfalls and imaging contribution in a real-world, institutional case series - Vicino, Alex; Hottinger, Andreas F.; Latifyan, Sofiya; Boughdad, Sarah; Becce, Fabio; Prior, John O.; Kuntzer, Thierry; Brouland, Jean-Philippe; Dunet, Vincent; Obeid, Michel; Théaudin, Marie (Journal of neurology, 2024)
Background Immune checkpoint inhibitors (ICIs) are reshaping the prognosis of many cancers, but often cause immune-related adverse events (irAEs). Among neurological irAEs, myositis is the most frequently reported. Our aim is to describe clinical and non-clinical characteristics, treatment and outcome of all irMyositis (skeletal limb-girdle and/or ocular myositis) and irMyocarditis cases in our reference center. Methods We retrospectively enrolled all irMyositis/irMyocarditis patients seen between 2018 and 2022. We reviewed demographics, clinical characteristics, biological, neurophysiological, imaging workup, treatment and outcome. Results We included 14 consecutive patients. The most frequent treatments were pembrolizumab (35%) or ipilimumab–nivolumab combination (35%). Limb-girdle, ocular (non-fluctuating palpebral ptosis and/or diplopia with or without ophthalmoparesis) and cardiac phenotypes were equally distributed, overlapping in 40% of cases. Ocular involvement was frequently misdiagnosed; review of brain MRIs disclosed initially missed signs of skeletal myositis in one patient and ocular myositis in 3. Seven patients had other co-existing irAEs. When performed, myography showed a myogenic pattern. CK was elevated in 8/15 patients, troponin-T in 12/12 and troponin-I in 7/9 tested patients. ICI were discontinued in all cases, with further immunosuppressive treatment in nine patients. In most cases, neurological and cardiological outcome was good at last follow-up. Conclusion Myositis is a potentially severe irAE. Despite its heterogeneous presentation, some highly suggestive clinical symptoms, such as ocular involvement, or radiological signs should raise physicians’ attention to avoid misdiagnosis. We thus recommend a multidisciplinary assessment (including complete neuromuscular evaluation) even in case of isolated myocarditis. Our series underlines the importance of an early diagnosis, since suspension of ICI and adequate treatment are usually associated with good functional outcome.